2023
DOI: 10.1007/s00217-023-04238-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antioxidant and antimicrobial activities of whole flours obtained from different species of Triticum genus

Abstract: Whole wheat is an exceptional source of phenolic compounds representing a promising phytochemical class to prevent diet-related chronic diseases thanks to its antioxidant activities. The present work reports the phenolic profile, the antioxidant capacity, the antimicrobial activity and the effect on Lactobacillus brevis growth of eight whole flours obtained from four ancient and modern wheat genotypes of Italian Triticum genus. Total phenolic content (TPC) and total flavonoid content (TFC) were quantified, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Moreover, phenolic acids promote the production of proteins that limit tumor growth, including phosphatase, p53, and the tensin homolog PTEN [107]. Several investigations have demonstrated that p-coumaric acids have antibacterial, anti-inflammatory, and anticancer properties [108][109][110]. For instance, Janicke et al [110] found that p-coumaric acid inhibited the growth of Caco-2 colon cancer cells in the cell cycle, hence protecting against the development of colon cancer.…”
Section: Health Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, phenolic acids promote the production of proteins that limit tumor growth, including phosphatase, p53, and the tensin homolog PTEN [107]. Several investigations have demonstrated that p-coumaric acids have antibacterial, anti-inflammatory, and anticancer properties [108][109][110]. For instance, Janicke et al [110] found that p-coumaric acid inhibited the growth of Caco-2 colon cancer cells in the cell cycle, hence protecting against the development of colon cancer.…”
Section: Health Potentialmentioning
confidence: 99%
“…p-Coumaric acid Antimicrobial, Anti-inflammatory, anticancer [108][109][110] Ferulic acid Anticancer, antihypertensive, antidiabetes, anti-inflammatory [111][112][113][114][115] Caffeic acid Antimutagenic, anticarcinogenic [116] Sinapic acid Antioxidative, anti-inflammatory, anticancer, antidiabetic, anti-neurodegeneration, anti-anxiety [120][121][122][123][124][125] p-Hydroxybenzoic acid Antithrombotic and anticoagulant [130,131]…”
Section: Phenolic Acid Health Potential Referencesmentioning
confidence: 99%